The role of investment climate indicators in stimulating economic growth: a standard study For Malaysia 1990-2016 - ذنون مروان عبد المالك; حسن محمد وحيد (Journal of Economics and Administrative Sciences, 2019)
In globalization, the world became open area to competition for the attractive of investment, and the abilities of each country to win the confidence of investors depend upon the preparation to optimize circumstances. The competitiveness is an essential means of expanding the capacity of developed to coexist in an international environment characterized by globalization. While competition describes the market structure, the behavior of investors and business, competitiveness is interested in the evaluation of business performance or countries and compare them in the conditions of competition available in these markets. Regarding Malaysia, which is depend on FDI-Export- Led Growth strategy, it has taking on different degrees and gradually the market economy through policies of privatization, trade liberalization, stimulating direct investment and institutions rehabilitation to improve competitiveness. We will try through this article to come within reach of the competitive position of the Malaysian economy through competitiveness indicators, providing the most important features of investment climate in Malaysia and trying to make proposals in order to improve the competitiveness of the national economy in order to ensure it in the level of international markets.